2006
DOI: 10.1080/10236240600919796
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of a hawksbill turtle data-logged during the passage of hurricane Georges through the Caribbean

Abstract: Recent severe hurricanes in the Caribbean and south-east United States have had devastating socioeconomic effects, and there is a pressing need to learn how animals are impacted by such events. We serendipitously deployed a multi-channel data logger onto a hawksbill turtle (Eretmochelys imbricata) during the breeding season in 1998 and logged various aspects of her behaviour before, during and after passage of hurricane Georges. As Georges passed by, the turtle made shorter dives, became more active and spent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…obs. ), possibly in order to use these for shelter (van Dam & Diez 1997a, Storch et al 2006) and maximize dive duration by employing these as a roof to counteract the positive buoyant affect of inhaled air (Houghton et al 2003). The ultrasonic telemetry signals are known to be blocked when the transmitter is surrounded by structures such as rock reef and raised corals (Arendt et al 2001, Mitamura et al 2005, Yokota et al 2006, Kawabata et al 2008.…”
Section: Diel Behavioral Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…obs. ), possibly in order to use these for shelter (van Dam & Diez 1997a, Storch et al 2006) and maximize dive duration by employing these as a roof to counteract the positive buoyant affect of inhaled air (Houghton et al 2003). The ultrasonic telemetry signals are known to be blocked when the transmitter is surrounded by structures such as rock reef and raised corals (Arendt et al 2001, Mitamura et al 2005, Yokota et al 2006, Kawabata et al 2008.…”
Section: Diel Behavioral Patternsmentioning
confidence: 99%
“…These results suggest that the head-started turtles were resting during the nocturnal period, but that their resting places were not as surrounded by structures as were those of the wild turtles. This could mean that head-started turtles will be carried away by strong currents under hazardous sea conditions such as a hurricane, or consume unnecessary energy in order to remain in the same place as opposed to wild turtles, which probably take shelter during hurricanes (Storch et al 2006). In addition, head-started turtles might not maximize their dive duration, because they have positive buoyancy in shallow water when they breathe fully (Houghton et al 2003).…”
Section: Diel Behavioral Patternsmentioning
confidence: 99%
“…It would therefore seem that sea turtles tend to optimize energy reserves in a way best suited to local environmental conditions (Houghton et al, 2002) and, when inter-nesting sea turtles are exposed to storms or hurricanes, it could be expected to cause changes in their behavior to cope with the severe oceanographic conditions. Two studies have examined the effect of severe weather conditions on the behavior of a loggerhead turtle (Sakamoto et al, 1990b) and a hawksbill turtle (Storch et al, 2006). Both studies found changed swimming behavior by turtles during the storm passage.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies found changed swimming behavior by turtles during the storm passage. The hawksbill encountering hurricane George in the Caribbean made shorter dives and spent less time at the surface (Storch et al, 2006). A loggerhead turtle encountering a typhoon made more dives and increased the dive depth and time spent at depth to avoid the wave action (Sakamoto et al, 1990b).…”
Section: Introductionmentioning
confidence: 99%
“…The hawksbill is a shallow diver that rarely descends beyond 15m (e.g. van Dam and Diez, 1996;Storch et al, 2006).…”
Section: Introductionmentioning
confidence: 99%